3D-printed microfluidic device with in-line amperometric detection that also enables multi-modal detection. Issue 15 (27th March 2020) - Hayter, Elizabeth A.; Castiaux, Andre D.; Martin, R. Scott
Abstract : A 3D-printed microfluidic device with amperometric detection employs a parallel-opposed electrode configuration, with threaded electrodes being in contact with the flow stream. This makes downstream detection of ATP via chemiluminescence possible. Abstract : Microfluidic amperometric detectors often include a reservoir to house auxiliary and reference electrodes, making subsequent detection downstream challenging. Here, we present an in-line microfluidic device with amperometric detection that incorporates a three-electrode set-up, made possible by threading electrodes into a 3D-printed flow cell. The electrodes consist of a commercially available threaded reference electrode and electrodes fabricated in commercially available fittings. This approach centers the working electrode in the fluidic channel enabling the use of a pillar working electrode that is shown to increase sensitivity, as compared to a traditional thin-layer electrode. In addition, the working and auxiliary electrodes can be directly opposed, with this configuration leading to a more uniform potential being applied to the working electrode as well as fewer issues with any iR drop. To demonstrate the ability to incorporate a separate mode of detection downstream from the electrochemical flow cell, the device is modified to include a mixing T for introduction of reagents for chemiluminescent detection of ATP ( via the luciferin–luciferase reaction), leading to a single 3D-printed device that can be used to detect norepinephrine and ATP, nearly simultaneously, by amperometry and chemiluminescence, respectively. This approach opens numerous possibilities, where microfluidics with in-line amperometry can be used in continuous circulation studies or in conjunction with other downstream detection events to study complex systems.